GAMBARAN KUALITAS HIDUP LANSIA DI WILAYAH KERJA PUSKESMAS BOJONG I KABUPATEN PEKALONGAN - Aniyati, Sri; Kamalah, Aisyah Dzil (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
Elderly is the last stage of development of human life. Elderly often experience physical, psychological, social or problems with the environment around them. This is make an affects in elderly’re quality of life. This study aims to determine the quality of life of the elderly who live in working area of puskesmas Bojong I Kabupeten Pekalongan. This research uses descriptive quantitative research design. Researchers describe QAL elderly by using a WHOQAL measuring instrument is a Quality Of Life (QAL) by WHO. The Quality Of Life (QAL) picture of the elderly in the working area of the Puskesmas Bojong I is largely adequate (74%). (72%) is sufficient, social (74%) enough and environment (64%) enough. In the future, efforts can be made to improve the quality of life of the elderly both physically, psychologically, socially and environmentally.